Organizational Capacity Of Educational Office In The Field Of Teachers And Educational Personnel Of West Java Province In The Placement Of Pppk Teachers - Angga Agustian; Rita Myrna; Nina Karlina (Dinasti Publisher, 2025)
In 2001, the placement of PPPK teachers who had passed the PPPK selection was carried out in stages. During stages 3 and 4, the GTK division was given the authority to place and relocate PPPK teachers. However, in practice, issues were causing 1,000 out of 3,800 teachers (stage 3) and 1,000 out of 4,850 teachers (stage 4) to be assigned to inappropriate locations. Therefore, adequate organizational capacity is required. Organizational capacity is the ability of an organization to utilize its resources to solve problems and achieve established goals. This research was conducted at the West Java Provincial Education Office to determine the organizational capacity of the West Java Provincial Education Office in the field of Teachers and Education Personnel for placing PPPK teachers. This research uses a qualitative approach with a descriptive research method, employing data collection techniques from observations, documentation, and in-depth interviews with GTK staff who have authority over the placement of PPPK teachers. The results of this research are described based on the components of organizational capacity according to Horton et al. (2003), which consist of human resources, infrastructure, technology, financial resources, strategic leadership, program and process management, and cooperation and relations with other parties. he research results indicate that the organizational capacity in the Department of Education of West Java Province in the Teacher and Education Personnel Division (GTK) does not yet fully meet all five organizational capacity factors by Horton et al. in the placement of PPPK teachers. The unmet capacities include human resources, technology, cooperation, and relations. Meanwhile, the capacities for process and strategic leadership are considered fulfilled. The author concludes that the unmet capacities are due to the limited competence of employees, which affects other capacities